2009
DOI: 10.1590/s0102-311x2009000800015
|View full text |Cite
|
Sign up to set email alerts
|

Are environmental pollutants risk factors for low birth weight?

Abstract: The aim of this study was to assess the association between prenatal exposure to air pollutants and low birth weight in a medium-sized city. An ecological study was performed, using live birth data from São José dos Campos, São Paulo State, Brazil. The environmental data were obtained from the São Paul State Environmental Agency. The study included full-term newborns whose mothers were 20 to 34 years of age and had at least a complete high school education, seven or more prenatal visits, singleton pregnancy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
0
26
0
5
Order By: Relevance
“…V). A significant association between risk of low birth weight and exposure to pollutants was found, like PM 10 , CO [98,112,118], SO 2 and O 3 [107]. A research [108] also revealed a gradient of approximately 50% of increasing risk of early neonatal death with higher exposure to traffic-related air pollution, compared with those less exposed.…”
Section: Regional -Regional Environmental Factorsmentioning
confidence: 83%
“…V). A significant association between risk of low birth weight and exposure to pollutants was found, like PM 10 , CO [98,112,118], SO 2 and O 3 [107]. A research [108] also revealed a gradient of approximately 50% of increasing risk of early neonatal death with higher exposure to traffic-related air pollution, compared with those less exposed.…”
Section: Regional -Regional Environmental Factorsmentioning
confidence: 83%
“…As far as concerns this last issue, it is enough to say that the reviewed data derive from very different countries such as the Czech Republic (Bobak, 2000;Bobak and Leon, 1999;Dejmek et al, 2000), Poland (Edwards et al, 2010), England (Dolk et al, 2010;Lee et al, 2008;Rankin et al, 2009), Spain Llop et al, 2010), Sweden (Landgren, 1996), Norway (Madsen et al, 2010), Holland , China (Jiang et al, 2007;Wang et al, 1997), the United States (Bell et al, 2007;Gray et al, 2009;Maisonet et al, 2001;Morello-Frosch et al, 2010;Parker et al, 2005;Rogers and Dunlop, 2006;Salam et al, 2005;Wilhelm and Ritz, 2005;Xu et al, 2010), South Korea (Ha et al, 2001;Lee et al, 2003;Seo et al, 2010), Taiwan (Lin et al, 2004;Yang et al, 2003), Canada Dugandzic et al, 2006;Liu et al, 2003), Brazil (Gouveia et al, 2004;Nascimento and Moreira, 2009;Pereira et al, 1998), and Australia (Hansen et al, 2009;Hansen et al, 2007;Mannes et al, 2005). In addition, other sources of bias can be represented by the residential mobility of the pregnant women (Canfield et al, 2006), although some studies minimize or even exclude this issue (Hodgson et al, 2009;Lupo et al, 2010;…”
Section: Discussionmentioning
confidence: 99%
“…This database was analyzed in two ways: unadjusted analysis: all preterm infants, without any selection or exclusion criteria; and adjusted analysis, with only those premature births by mothers between 18 and 34 years old, resulting from a single pregnancy, whose delivery was vaginal and whose mothers had at least eight years of schooling in order to minimize the effects of these potential confounders. This approach was used in another study (Nascimento and Moreira, 2009).…”
Section: Methodsmentioning
confidence: 99%